2022
DOI: 10.1088/1755-1315/982/1/012008
|View full text |Cite
|
Sign up to set email alerts
|

Ferrochrome Slag characterization and its compatibility with Quarry dust in Flexible pavement

Abstract: Exhaustion of locally available materials and increasing hauling charges gained the potential for the exploration of cost-effective alternative materials in the construction industry. Broad endeavours have been made over numerous years on the utilization of industrial waste, yet scant exploration is being done on ferrochrome slag. Ferrochrome slag is an industrial by-product obtained from stainless steel production. Several highway laboratory tests on the characterization of ferrochrome slag are carried out, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…In recent years, many studies are conducted based on utilization of quarry dust for construction purpose [20]. The ferrochrome slag was used along with quarry dust as alternative to conventionally used aggregates in pavement, it was found that the ferrochrome slag and quarry dust mix can be effectively used base and subbase of flexible pavement [21]. Stabilization of soft subgrade was attempted using quarry dust and it was observed that addition of quarry dust to soft soil yielded in higher CBR compared to untreated soil [22].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many studies are conducted based on utilization of quarry dust for construction purpose [20]. The ferrochrome slag was used along with quarry dust as alternative to conventionally used aggregates in pavement, it was found that the ferrochrome slag and quarry dust mix can be effectively used base and subbase of flexible pavement [21]. Stabilization of soft subgrade was attempted using quarry dust and it was observed that addition of quarry dust to soft soil yielded in higher CBR compared to untreated soil [22].…”
Section: Introductionmentioning
confidence: 99%